Implementation of a bluetooth attack on controller area network (CAN) - Zniti Asmae; El Ouazzani Nabih (Institute of Advanced Engineering and Science, 2021)
In this paper a general overview of the vulnerability of the CAN bus is presented and a practical short-range attack is proposed. There are more and more potential attacks on the CAN bus, which may cause leakage of information and thereby there may be danger for safe driving. The attack combines several techniques, such as how to update a node firmware using a Bluetooth module and inject a priority fake frame, in order to block the legitimate messages.